In Case You Haven't Heard… (Alcoholism & Drug Abuse Weekly, 2021)
You can't have missed all the headlines last week saying that coffee is good for your liver, it can counteract the effects of drinking alcohol and so on. Yes, there is a study that found an association between reduced liver disease and coffee consumption. However, the headlines — and most of the articles (all the ones we read, but we're being generous and assuming some will get it right) — ignored the Limitations section (if they even read the study itself), which includes this sentence: “A limitation is the observational cohort design, which cannot infer causation.” There was no “but” after this sentence. For the actual study, go to https://bmcpublichealth.biomedcentral.com/articles/10.1186/s12889‐021‐10991‐7 . And by the way, if you drink alcohol and coffee, all you are doing is giving your gut a double whammy of an insult.